DIAGNOSTIC IMAGING OF BONE SARCOMAS OF THE PELVIC GIRDLE - L. S. Sapunova; I. G. Frolova; S. A. Velichko; A. V. Bogoutdinova; О. V. Kotova; E. E. Bober (Сибирский онкологический журнал)
Diagnostic imaging of bone sarcomas of the pelvic girdle using computed tomograpgy, sonography and scintigraphy was performed on 59 patients with the aim to determine the precise tumor localization and to assess tumor spread. Features of tumor spread into the pelvic bones involving all layers of the bone were found. The main trends in spread of soft tissue component in bones of the pelvic girdle were studied.